2019
DOI: 10.1136/ejhpharm-2019-001987
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of error: a review of wrong dose medication incidents reported to a UK hospital voluntary incident reporting system

Abstract: ObjectivesOur aim was to review medication-related incidents reported to a hospital voluntary incident reporting system to identify and quantify the magnitude of wrong dose errors.MethodsThe study was a retrospective review of medication-related incidents reported over a 7-year period at a large acute teaching hospital in the UK, providing secondary and tertiary care for a range of clinical specialties. Medication-related incident reports submitted from all clinical settings were reviewed. Incidents submitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
(39 reference statements)
0
6
0
1
Order By: Relevance
“…It is worth mentioning that overdoses are more likely to be identified, intercepted, and reported than underdoses, as they can be perceived as having greater potential for patient harm. However, all drug doses should be prescribed in accordance with clinical guidance and dispensed and administered exactly as prescribed, since the potential for patient harm associated with dosing errors is difficult to predict and varies according to a number of factors, including the magnitude of the error, the toxicity profile of the drug itself, the clinical status of the patient, and the tolerance or susceptibility to the effect of the drug 27 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that overdoses are more likely to be identified, intercepted, and reported than underdoses, as they can be perceived as having greater potential for patient harm. However, all drug doses should be prescribed in accordance with clinical guidance and dispensed and administered exactly as prescribed, since the potential for patient harm associated with dosing errors is difficult to predict and varies according to a number of factors, including the magnitude of the error, the toxicity profile of the drug itself, the clinical status of the patient, and the tolerance or susceptibility to the effect of the drug 27 .…”
Section: Discussionmentioning
confidence: 99%
“…É interessante mencionar que sobredosagens são mais prováveis de serem identificadas, interceptadas e notificadas que as subdosagens, pois podem ser percebidas como tendo maior potencial de dano ao paciente. Contudo, todas as doses de medicamentos devem estar prescritas de acordo com a orientação clínica e ser dispensadas e administradas exatamente como prescrito, uma vez que o potencial de dano ao paciente associado a erros de dose é difícil de prever e varia de acordo com uma série de fatores, incluindo a magnitude do erro, o perfil de toxicidade do próprio medicamento, o estado clínico do paciente e a tolerância ou suscetibilidade ao efeito do medicamento 27 .…”
Section: Considerações Finaisunclassified
“…Evidence suggests that medication errors are more likely to occur in children than in adults and may be up to three times more likely to cause harm 3–5. Voluntary incident reporting has been used to monitor medication errors and related patient safety risks in hospitals around the world 6 7. A retrospective study of medication errors in children submitted to the US Pharmacopeia’s Medication Errors Reporting Program found that 31% of the errors were cited as harmful or fatal 8…”
Section: Introductionmentioning
confidence: 99%